SA to optimize the Multi-Period Water Distribution Network Design - Bermúdez, Carlos (2018)
The design optimization of the water distribution network is an important issue in modern cities. For this reason, we propose an optimization technique based on Simulated Annealing (SA) to solve the Water Distribution Network Design problem, considering multi-period restrictions with time varying demand patterns. The SA is improved with a local search procedure, yielding a hybrid SA, in order to obtain good quality networks designs. A broad experimentation using different test networks is carried out to test our proposal. Moreover, a comparison with an approach from the literature reveals the goodness of our proposal, the hybrid SA.